2016
DOI: 10.1186/s40792-015-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondary abdominal compartment syndrome required decompression laparotomy during minimally invasive mitral valve repair

Abstract: We treated a 77-year-old patient with secondary abdominal compartment syndrome that caused failure to maintain cardiopulmonary bypass while undergoing elective minimally invasive right mini-thoracotomy mitral valve and tricuspid valve repair procedures. During the operation, a decompression laparotomy was needed to relieve elevated intraabdominal pressure that caused instability of the cardiopulmonary bypass. Due to poor oxygenation and the long cardiopulmonary bypass time, the patient required peripheral extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Recently, a prospective observational multicenter study reported one percent of cardiac surgery patients developed ACS post-operatively and require decompressive laparotomy, with significant associated mortality of 57% ( 13 ). We could only identify two prior case reports describing the development of intraoperative ACS during cardiac surgery: (1) secondary ACS during failure to maintain CPB while undergoing elective minimally invasive right mini-thoracotomy mitral valve and tricuspid valve repairs ( 14 ). In this report, the authors reported a “relatively long period of time was needed to make a diagnosis of ACS” as automated other potential causes of hemodynamic instability were assessed ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a prospective observational multicenter study reported one percent of cardiac surgery patients developed ACS post-operatively and require decompressive laparotomy, with significant associated mortality of 57% ( 13 ). We could only identify two prior case reports describing the development of intraoperative ACS during cardiac surgery: (1) secondary ACS during failure to maintain CPB while undergoing elective minimally invasive right mini-thoracotomy mitral valve and tricuspid valve repairs ( 14 ). In this report, the authors reported a “relatively long period of time was needed to make a diagnosis of ACS” as automated other potential causes of hemodynamic instability were assessed ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…We could only identify two prior case reports describing the development of intraoperative ACS during cardiac surgery: (1) secondary ACS during failure to maintain CPB while undergoing elective minimally invasive right mini-thoracotomy mitral valve and tricuspid valve repairs ( 14 ). In this report, the authors reported a “relatively long period of time was needed to make a diagnosis of ACS” as automated other potential causes of hemodynamic instability were assessed ( 14 ). (2) Rabbi et al described another secondary ACS occurring during elective coronary revascularization, resulting in the inability to wean off CPB ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the IAP measurement using intravesical pressure is important for the diagnosis of ACS [8], it is not always measured for the diagnosis of ACS. Considerable increase of IAP was confirmed solely by external physical finding with percutaneous needle decompression for tension pneumoperitoneum [9] and with a decompression laparotomy [10] in previously reported ACS cases. In the present case, muscular defense by peritonitis was unlikely based on the autopsy findings, and the severely distended abdominal surface was extremely stiff despite the use of a muscle relaxant.…”
Section: Discussionmentioning
confidence: 99%
“…23 Abdominal compartment syndrome requiring emergency surgical decompression has also been reported by several groups. 24,25 We experienced 1 case of retrograde aortic dissection caused by guide-wire injury to the iliac artery. That surgery was aborted and the patient underwent an MV repair through a standard sternotomy 1 year later after conservative treatment.…”
Section: Study Limitationsmentioning
confidence: 99%